MOFs-porous microsphere composite material as well as preparation method and application thereof
A MOFs-porous microsphere composite material addresses the inefficiency of existing cigarette filter additives by enhancing nicotine removal through a structured composite of fumed silica, cellulose, and phthalocyanine, achieving high adsorption capacities for nicotine and 3-vinylpyridine in environmental smoke.
Patent Information
- Application Number
- CN202411522251.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-31
AI Technical Summary
Existing cigarette filter additives are ineffective in specifically targeting and removing nicotine from environmental smoke due to poor adsorption performance and lack of specificity, particularly in the gas phase.
A MOFs-porous microsphere composite material is developed, comprising amino-modified porous microspheres with MOFs formed on their surface, using fumed silica, cellulose, and phthalocyanine as raw materials, with a specific ratio and structure to enhance physical and chemical adsorption of nicotine.
The composite material achieves high adsorption capacities for nicotine and 3-vinylpyridine, with saturated adsorption up to 300 mg/g, effectively improving the removal of these components from environmental smoke.
Smart Images

Figure CN119215866A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of porous adsorption materials, and in particular to a MOFs-porous microsphere composite material and a preparation method and application thereof. Background Art
[0002] Environmental smoke is a type of substance produced in indoor air due to smoking tobacco products, mainly including sidestream smoke released from the combustion cone between two puffs and mainstream smoke exhaled by smokers. The indicators of concern for environmental smoke generally include VOCs, formaldehyde, nitrogen oxides and nicotine. VOCs, formaldehyde and nitrogen oxides are common indoor pollutants and atmospheric pollutants, while nicotine is a relatively unique compound, which mainly exists in the form of gas phase in environmental smoke. Using an air purifier is a common means of purifying environmental tobacco smoke. At present, the research and development of air purification technology at home and abroad mainly focuses on physical adsorption and chemical catalysis. The commonly used functional materials for physical adsorption include activated carbon, zeolite molecular sieves, organic silica and fibers, and the chemical catalysis mainly involves photocatalytic oxidation. In general, in terms of indoor air purification, the current large-scale industrial use is mainly physical adsorbents such as activated carbon and molecular sieves, which mainly target conventional air pollutants such as VOCs, but lack specificity for nicotine.
[0003] When cigarette smoke is transmitted in the filter, nicotine exists in both the gas phase and the particle phase. As the smoke is further transmitted in the filter, the proportion of nicotine in the particle phase gradually increases, and finally exists in the mainstream smoke in the particle phase. Therefore, the removal of nicotine by cigarette filter additives is mainly achieved through physical collision, interception, diffusion, physical adsorption, etc. For example, Yuan Shuxia et al. used nitric acid-modified activated carbon in cigarette filters, and the adsorption capacity of nicotine and tar increased by 25.6% and 8.8% respectively (Effect of Activated Carbon Modification on Filter Adsorption Performance [J], Journal of Taiyuan University of Technology, 2007, 38 (6): 509-512). For example, Wang Chenhui et al. investigated the effect of melon rings on the retention of nicotine in mainstream cigarette smoke. When the dosage of melon rings was 20 mg, the retention of tar and nicotine was 46.1% and 60.3%, respectively (Study on the Retention Effect of Melon Rings on Tar and Nicotine in Mainstream Cigarette Smoke [J], Journal of Guizhou University, 2012, 29 (2): 16-19).
[0004] However, nicotine mainly exists in the form of gas phase in environmental smoke. Using existing cigarette filter additives to remove nicotine has problems such as poor adsorption performance and lack of targeting, making it difficult to effectively remove nicotine in environmental smoke. Therefore, it is extremely necessary to develop a material for removing nicotine from environmental smoke. Summary of the invention
[0005] In view of this, the main purpose of the present invention is to provide a MOFs-porous microsphere composite material and a preparation method and application thereof, which can effectively remove nicotine in environmental smoke.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A MOFs-porous microsphere composite material comprises amino-modified porous microspheres and MOFs (metal organic framework compounds) formed on the surface of the amino-modified porous microspheres, wherein the amino-modified porous microspheres comprise porous microspheres with fumed silica, cellulose and phthalocyanine as main raw materials, and the cellulose therein is introduced with amino groups by reacting with urea; the MOFs are mainly formed by in-situ growth on the surface of the amino-modified porous microspheres with pyridine carboxylic acid ligands and metal salts as raw materials, and the metal ions in the metal salts are fixed to the amino-modified porous microspheres through the amino groups introduced on the cellulose.
[0007] The particle size of the porous microspheres is preferably 1.0 to 1.5 mm, and they are mainly used as the skeleton structure of the composite material, in which the main raw materials, fumed silica, cellulose and phthalocyanine, are bonded together by a water-resistant adhesive. The fumed silica includes a number of through holes, has a high specific surface area, can provide a passage for the transmission of environmental smoke, and has a strong physical adsorption function for environmental smoke such as nicotine. If the amount of fumed silica is too small, its pore channels may be blocked by cellulose, copper phthalocyanine and adhesive, resulting in a reduction in pores, which is not conducive to subsequent modification; if the amount of fumed silica is too large, the amount of copper such as cellulose will be reduced, which is not conducive to the subsequent in-situ growth of MOFs and affects the chemical adsorption of nicotine by the material.
[0008] The particle size of the cellulose is ≤50 μm, and its main function is to provide a carrier for the subsequent in-situ growth of MOFs. If the amount is too small, it is not conducive to the subsequent in-situ growth of MOFs, and affects the chemical adsorption of the composite material to environmental smoke such as nicotine and 3-vinyl pyridine; if the amount is too large, it may block the pore channels of the fumed silica, resulting in a reduction in pores, which is not conducive to subsequent modification. The main function of the phthalocyanine is to remove components such as nicotine and 3-vinyl pyridine. If the amount is too small, the effect of removing environmental smoke such as nicotine and 3-vinyl pyridine is not significant; if the amount is too large, it may block the pore channels of the fumed silica, resulting in a reduction in pores, which is not conducive to subsequent modification. Therefore, the fumed silica, cellulose and phthalocyanine in the porous microspheres cooperate with each other and work synergistically to promote the chemical adsorption of environmental smoke such as nicotine and 3-vinyl pyridine, and effectively remove environmental smoke such as nicotine and 3-vinyl pyridine. Therefore, the mass ratio of the fumed silica, cellulose and phthalocyanine is (45-60):(30-45):(5-8).
[0009] The fumed silica is preferably hydrophobic fumed silica, preferably with a high specific surface area such as 200 to 300 m 2 / g of hydrophobic fumed silica. The phthalocyanine may be a metal phthalocyanine, including copper phthalocyanine, iron phthalocyanine, etc., preferably copper phthalocyanine.
[0010] If the amount of water-resistant binder in the porous microspheres is too little, the porous microspheres may fall into powder; if too much, the pore channels of the fumed silica may be blocked, resulting in a reduction in pores, which is not conducive to subsequent modification. Therefore, the water-resistant binder is 3% to 7% of the mass of the porous microspheres; preferably, 5%.
[0011] The main function of urea is to introduce amino groups into cellulose. If the amount of urea is too small, it is not conducive to the subsequent chemical modification and affects the adsorption of environmental smoke such as nicotine and 3-vinylpyridine. The maximum theoretical degree of substitution of cellulose esterification is 3. If the amount of urea is too large and exceeds this range, it may be not conducive to the subsequent chemical modification, resulting in reduced reaction efficiency and affecting the adsorption of environmental smoke such as nicotine and 3-vinylpyridine. Therefore, the molar ratio of urea to cellulose in the porous microspheres is preferably 1:1 to 3:1.
[0012] The metal ions in the pyridine carboxylic acid ligands and metal salts are the main raw materials for synthesizing MOFs. The amino groups in the amino-modified porous microspheres can immobilize metal ions by complexing with the metal ions in MOFs, and can also be used for deprotonation of carboxylic acid ligands so that MOFs can grow in situ. Therefore, if the amount of metal ions is too small, the in situ growth of MOFs may be limited, affecting the removal effect of environmental smoke such as nicotine and 3-vinylpyridine. If the amount is too large, some MOFs may grow by themselves and fail to be immobilized on the porous microspheres, and be washed away during post-washing treatment, affecting the removal effect of environmental smoke such as nicotine and 3-vinylpyridine. Therefore, the molar ratio of the amino groups in the amino-modified porous microspheres, the carboxyl groups in the pyridine carboxylic acid ligands, and the metal ions in the metal salts is preferably 1:1:(1-1.5). Among them, the pyridine carboxylic acids include pyridine-2,5-dicarboxylic acid, pyridine-2,4,6-tricarboxylic acid, etc., preferably pyridine-2,5-dicarboxylic acid. The metal salt is a soluble metal salt, including a soluble copper salt, a soluble iron salt, such as copper sulfate, iron sulfate, and the like.
[0013] The present invention also provides a method for preparing the above MOFs-porous microsphere composite material, comprising the steps of: S1. Preparation of porous microspheres: using fumed silica, cellulose and phthalocyanine as main raw materials to prepare porous microspheres; S2, amino modification: uniformly mixing the porous microspheres with an aqueous urea solution and heating and drying, and then performing a dry amino modification reaction to obtain amino-modified porous microspheres; S3, in situ growth of MOFs: adding the amino-modified porous microspheres and pyridine carboxylic acid ligands to a metal salt aqueous solution, heating and stirring until the pyridine carboxylic acid ligands are completely dissolved, cooling to room temperature to react, and obtaining a MOFs-porous microsphere composite material.
[0014] The step S1 specifically includes the steps of: uniformly mixing fumed silica, cellulose, phthalocyanine and a water-resistant adhesive, and preparing the porous microspheres by an extrusion spheronization method.
[0015] The step S2 specifically includes the steps of: firstly, uniformly mixing the porous microspheres with the urea aqueous solution, and drying them by rotary evaporation until the moisture content is less than 10%, and then performing a dry amino modification reaction at 130°C to 170°C for 2 to 8 hours to obtain the amino-modified porous microspheres. The dry amino modification reaction temperature is preferably 140°C to 170°C, such as 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, etc. The dry amino modification reaction time is preferably 4 to 7 hours, such as 4 hours, 5 hours, 6 hours, 7 hours, etc.
[0016] The step S3 specifically includes the steps of: firstly adding the amino-modified porous microspheres and the pyridine carboxylic acid ligands to the metal salt aqueous solution in sequence, heating and stirring at 45°C to 55°C until the pyridine carboxylic acid ligands are completely dissolved, cooling to room temperature for reaction, filtering, washing with water, and vacuum drying to obtain the MOFs-porous microsphere composite material. Among them, the room temperature reaction time is preferably 2 to 5 d (days), such as 2, 3, 4, 5 d, etc. In this step, the metal ions in the metal salt aqueous solution are immobilized on the porous carbon spheres by reacting with the amino groups, and the amino-modified porous microspheres deprotonate the carboxylic acid ligands, and the deprotonated carboxylic acid ligands react with the metal ions immobilized on the porous carbon spheres to generate MOFs in situ.
[0017] According to experiments, the saturated adsorption capacity of nicotine and 3-vinylpyridine of 1 g of MOFs-porous microsphere composite material are above 100 mg / g and 75 mg / g respectively. The saturated adsorption capacity of nicotine is preferably 100-300 mg / g, and more preferably 190-300 mg / g; the saturated adsorption capacity of 3-vinylpyridine is preferably 75-250 mg / g, and more preferably 190-250 mg / g.
[0018] Therefore, the present invention also provides an application of the above MOFs-porous microsphere composite material in the preparation of nicotine adsorption material.
[0019] The present invention also provides an application of the MOFs-porous microsphere composite material in preparing a 3-vinylpyridine adsorption material.
[0020] The present invention also provides an application of the above MOFs-porous microsphere composite material in the preparation of an environmental smoke purification material. The MOFs-porous microsphere composite material as an environmental smoke purification material can adsorb components such as nicotine and 3-vinylpyridine in environmental smoke, effectively improving the removal rate of gas-phase nicotine and 3-vinylpyridine.
[0021] The main reasons why the MOFs-porous microsphere composite material provided by the present invention can be used as an environmental flue gas purification material are as follows: (1) Physical adsorption: The fumed silica in the porous microspheres has the characteristics of high specific surface area and strong surface adsorption force. MOFs contain a large number of micropores and mesopores. Therefore, the MOFs-modified porous microsphere composite material with different pore shapes obtained by combining the porous microspheres and MOFs has a strong physical adsorption capacity and can effectively adsorb nicotine and 3-vinylpyridine in environmental smoke.
[0022] (2) Chemical adsorption: The amino groups in the amino-modified porous microspheres can be used to immobilize metal ions and deprotonate carboxylic acid ligands to facilitate in-situ growth of MOFs; the pyridine rings in MOFs can produce conjugated effects with environmental smoke components such as nicotine and 3-vinylpyridine, and the active metal ions in the composite material can complex with components such as nicotine and 3-vinylpyridine in environmental smoke, which is beneficial to the removal of components such as nicotine and 3-vinylpyridine in environmental smoke. In addition, phthalocyanine is a highly conjugated system and its benzene ring is a coplanar structure, which can produce conjugated effects with components such as nicotine and 3-vinylpyridine in environmental smoke, and cooperate with the pyridine rings in MOFs, which is beneficial to the removal of components such as nicotine and 3-vinylpyridine in environmental smoke.
[0023] Therefore, the specific surface area of the MOFs-porous microsphere composite material provided by the present invention is 200-650 m 2 / g, pore volume 0.120-0.342 cm 3 / g, with an average pore size of 6.5-8 nm, it has strong physical and chemical adsorption properties for environmental smoke components such as nicotine and 3-vinylpyridine, and can be used as an adsorption material for nicotine and 3-vinylpyridine, efficiently adsorbing nicotine and 3-vinylpyridine, and can also be used as an environmental smoke purification material, which can effectively remove nicotine and 3-vinylpyridine and other components in environmental tobacco smoke. In addition, the MOFs-porous microsphere composite material of the present invention has a microsphere-shaped morphology, which is convenient for industrial application, and the process conditions are mild, which makes it easier to achieve industrial production, and can be applied to air purification systems, intelligent smoking room purification systems and other scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1Schematic diagram of the preparation process of the MOFs-porous microsphere composite material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0026] The terms used in the present invention are all commonly used terms in the relevant field. The raw materials, equipment, preparation processes, testing methods, etc. used are all prior arts in the relevant field unless otherwise specified.
[0027] Examples 1-8 Embodiments 1 to 8 of the present invention each provide a MOFs-porous microsphere composite material, including amino-modified porous microspheres and MOFs formed on the surface of the amino-modified porous microspheres, wherein the amino-modified porous microspheres include porous microspheres made of fumed silica, fiber cellulose, copper phthalocyanine and Celanese Celvolit 1319 as adhesive, and the cellulose therein is introduced with amino groups by reacting with urea; the MOFs are mainly formed by in-situ growth on the surface of the amino-modified porous microspheres using 2,5-pyridinedicarboxylic acid and copper sulfate as raw materials, and the Cu 2+ The amino groups introduced into the cellulose are immobilized on the amino-modified porous microspheres. The fumed silica has a specific surface area of 220 to 250 m 2 / g of hydrophobic fumed silica, and the particle size of the cellulose is ≤50μm.
[0028] See also Figure 1 The preparation method of each of the above MOFs-porous microsphere composite materials comprises the following steps: (1) Preparation of porous microspheres The porous microspheres with a particle size of 1.0-1.5 mm were prepared by using fumed silica, cellulose, copper phthalocyanine and a binder as raw materials through an extrusion spheronization method.
[0029] (2) Amino modification The porous microspheres obtained in step (1) were mixed evenly with a 10% urea aqueous solution, dried by rotary evaporation at 50°C until the moisture content was less than 10%, and then dry-reacted at 150°C for 5 h to obtain amino-modified porous microspheres.
[0030] (3) In situ growth of MOFs Add copper sulfate pentahydrate to water and stir evenly to form a copper sulfate solution with a concentration of 0.3 mol / L; add the amino-modified porous microspheres obtained in step (2) and 2,5-pyridinedicarboxylic acid to the copper sulfate solution in sequence, heat and stir at 50°C until the ligand is dissolved, cool to room temperature and react for 3 days, filter, wash with water, and vacuum dry to obtain a MOFs-porous microsphere composite material.
[0031] Table 1 Material dosage of the examples (unit: g) Comparative Examples 1-7 each provide a MOFs composite material, and the preparation method thereof is substantially the same as that of the corresponding embodiment, with the main differences being as follows: Comparative Example 1: The masses of the fumed silica and cellulose in step (1) of Example 1 were adjusted to 40.0 g and 50.0 g, respectively, and the other conditions were the same as those of Example 1.
[0032] Comparative Example 2: The amount of 10% urea aqueous solution in step (2) of Example 8 was adjusted from 333.33 g to 388.9 g, the mass of amino-modified porous microspheres used for in-situ growth of MOFs was adjusted to 139 g, and the other conditions were consistent with Example 8.
[0033] Comparative Example 3: The molar ratio of amino group, carboxyl group and copper ion in step (3) of Example 3 was adjusted from 1:1:1.5 to 1:1:1.7, the copper sulfate concentration was still 0.3 mol / L, and other conditions were consistent with Example 3.
[0034] Comparative Example 4: The amount of fumed silica in step (1) of Example 1 was adjusted to 95 g, cellulose and copper phthalocyanine were removed, and porous microspheres were prepared. At the same time, the amino modification of step (2) was no longer performed. The mass of the in situ grown MOFs porous microspheres was 100 g, and the other conditions were consistent with Example 1.
[0035] Comparative Example 5: The amount of cellulose in step (1) of Example 2 was adjusted to 95 g, the fumed silica and copper phthalocyanine were removed, and microspheres were prepared. The other conditions were the same as those in Example 2.
[0036] Comparative Example 6: The amount of fumed silica in step (1) of Example 4 was adjusted to 87 g, and the cellulose was removed to prepare porous microspheres. At the same time, the amino modification of step (2) was no longer performed. The mass of the in situ grown MOFs porous microspheres was 100 g. The other conditions were consistent with Example 4.
[0037] Comparative Example 7: The amount of cellulose in step (1) of Example 2 was adjusted to 89 g, the fumed silica was removed, and microspheres were prepared. The other conditions were the same as those of Example 2.
[0038] The pore structures of the composite materials provided in Examples 1-8 and Comparative Examples 1-7 were analyzed using a specific surface area and pore size tester. The specific data are shown in Table 2.
[0039] Table 2 Pore structure of composite materials It can be seen from Table 2 that the specific surface area of the composite material provided by the embodiment of the present invention is 201-634 m 2 / g, pore volume 0.121-0.338 cm 3 / g, and an average pore diameter of 6.9-7.8 nm. Compared with the comparative examples, the composite material provided by the embodiment of the present invention has a higher specific surface area and a larger pore volume.
[0040] Adsorption performance verification This example provides the use of the MOFs-porous microsphere composite materials prepared in the above examples 1-8 and the MOFs composite materials provided in comparative examples 1-7 in the preparation of environmental smoke purification materials. This example uses a multi-component adsorption penetration curve analyzer to evaluate the adsorption performance of nicotine and 3-vinyl pyridine by 15 materials prepared in examples 1-8 and comparative examples 1-7, so as to prove that the MOFs-porous microsphere composite materials provided in the examples of the present invention can be used as environmental smoke purification materials, and can effectively remove nicotine and 3-vinyl pyridine in environmental smoke. The specific method is as follows: Nicotine evaluation experiment: Weigh about 1 g of purification material sample and fill it into a sample tube with an inner diameter of 10 mm. Purge and activate it with nitrogen at 50°C for 120 min, with a purge gas flow rate of 20 sccm. The experimental conditions were set at room temperature and pressure, the nicotine concentration was set to 55 ppm, the total air flow rate was 80 mL / min, and nitrogen was used as a carrier gas and did not participate in adsorption.
[0041] 3-vinylpyridine evaluation experiment: weigh about 1 g of the purification material sample and fill it into a sample tube with an inner diameter of 10 mm. Purge activation with nitrogen at 50°C for 120 min, with a purge gas flow rate of 20 sccm. The experimental conditions were set at room temperature and pressure, the 3-vinylpyridine concentration was set to 55 ppm, the total inlet flow rate was 80 mL / min, and nitrogen was used as a carrier gas and did not participate in adsorption. The evaluation results are shown in Table 3.
[0042] Table 3 Saturated adsorption of nicotine and 3-vinylpyridine by purification material samples It can be seen from Table 3 that the saturated adsorption capacity of nicotine and 3-vinylpyridine by 1 g of the MOFs-porous microsphere composite material provided in the embodiment of the present invention is 105-285 mg / g and 83-225 mg / g respectively. The saturated adsorption capacity of nicotine and 3-vinylpyridine by the purification materials prepared in different embodiments is quite different, and the main reason for this is that their physical and chemical structures are closely related.
[0043] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 1 are 81 mg / g and 65 mg / g, respectively, which are significantly lower than 105 mg / g and 83 mg / g of the purification material in Example 1. This is mainly due to the small amount of fumed silica and the excessive amount of cellulose used in Comparative Example 1, which may block the pores of the fumed silica, affect the diffusion of nicotine and 3-vinylpyridine in the microspheres, and cause a decrease in the saturated adsorption amount of nicotine and 3-vinylpyridine.
[0044] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 2 are 185 mg / g and 145 mg / g, respectively, which are significantly lower than 230 mg / g and 185 mg / g of the purification material in Example 8. This may be due to the excessive amount of urea used, which exceeds the maximum theoretical degree of substitution of cellulose, which is not conducive to subsequent chemical modification, resulting in reduced reaction efficiency and a decrease in the saturated adsorption amounts of nicotine and 3-vinylpyridine.
[0045] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 3 are 116 mg / g and 90 mg / g, respectively, which are significantly lower than 150 mg / g and 118 mg / g of the purification material in Example 3. This may be due to the excessive amount of copper ions used, which causes part of the MOFs to grow by themselves and fail to be immobilized on the porous microspheres. They are washed away during post-washing treatment, affecting the removal effect of nicotine and 3-vinylpyridine, resulting in a decrease in the saturated adsorption amount of nicotine and 3-vinylpyridine.
[0046] The saturated adsorption capacity of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 4 is 26 mg / g and 20 mg / g, respectively, which is much lower than that of Example 1. This may be because there is no cellulose in Comparative Example 4, and the subsequent MOFs cannot be effectively immobilized on the fumed silica, resulting in the loss of some MOFs during post-processing. At the same time, there is no copper phthalocyanine in the material. The combination of these two factors greatly affects the saturated adsorption capacity of nicotine and 3-vinylpyridine of the material.
[0047] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 5 are 15 mg / g and 12 mg / g, respectively, which are much lower than those in Example 2. This may be because there is no fumed silica in Comparative Example 5, and the microspheres prepared in step (1) basically do not have a porous structure, resulting in the subsequent amino modification and MOFs in-situ growth basically occurring on the surface of the microspheres, thus greatly reducing their physical and chemical adsorption functions. In addition, there is no copper phthalocyanine in the material. The combination of these two factors greatly affects the saturated adsorption amount of nicotine and 3-vinylpyridine by the material.
[0048] The saturated adsorption capacity of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 6 is 41 mg / g and 32 mg / g, respectively, which is much lower than that of Example 4. This may be because there is no cellulose in Comparative Example 6, and the subsequent MOFs cannot be effectively immobilized on the fumed silica, resulting in the loss of some MOFs during post-processing, which greatly affects the saturated adsorption capacity of nicotine and 3-vinylpyridine of the material.
[0049] The saturated adsorption amounts of nicotine and 3-vinylpyridine of the purification material provided in Comparative Example 7 were 17 mg / g and 13 mg / g, respectively, which were much lower than those in Example 2. This may be because there was no fumed silica in Comparative Example 7, and the microspheres prepared in step (1) basically had no porous structure, resulting in the subsequent amino modification and MOFs in-situ growth basically occurring on the surface of the microspheres. Therefore, the physical and chemical adsorption functions were greatly reduced, which greatly affected the saturated adsorption amount of nicotine and 3-vinylpyridine of the material.
[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A MOFs-porous microsphere composite material, characterized in that: The invention comprises amino-modified porous microspheres and MOFs formed on the surface of the amino-modified porous microspheres, wherein the amino-modified porous microspheres comprise porous microspheres with fumed silica, cellulose and phthalocyanine as main raw materials, and the cellulose therein is introduced with amino groups by reacting with urea; the MOFs are mainly formed by in-situ growth on the surface of the amino-modified porous microspheres with pyridine carboxylic acid ligands and metal salts as raw materials, and the metal ions in the metal salts are fixed to the amino-modified porous microspheres through the amino groups introduced on the cellulose; Preferably, the specific surface area of the composite material is 200-650 m 2 / g, pore volume 0.120-0.342 cm 3 / g, and the average pore size is 6.5-8 nm.
2. The composite material according to claim 1, characterized in that: The mass ratio of the fumed silica, cellulose and phthalocyanine is (45-60): (30-45): (5-8); Preferably, the particle size of the porous microspheres is 1.0-1.5 mm.
3. The composite material according to claim 2, characterized in that: The fumed silica is hydrophobic fumed silica, and the phthalocyanine is metal phthalocyanine; Preferably, the metal phthalocyanine is copper phthalocyanine or iron phthalocyanine; Preferably, the specific surface area of the hydrophobic fumed silica is 200 to 300 m 2 / g.
4. The composite material according to any one of claims 1 to 3, characterized in that: Based on 100 parts by mass, the water-resistant adhesive accounts for 3% to 7% of the mass of the porous microspheres.
5. The composite material according to any one of claims 1 to 3, characterized in that: The molar ratio of urea to cellulose in the porous microspheres is 1:1 to 3:
1.
6. The composite material according to any one of claims 1 to 3, characterized in that: The molar ratio of the amino group in the amino-modified porous microspheres, the carboxyl group in the pyridine carboxylic acid ligand and the metal ion in the metal salt is 1:1:(1-1.5).
7. The composite material according to claim 6, characterized in that: The pyridine carboxylic acid is pyridine-2,5-dicarboxylic acid or pyridine-2,4,6-tricarboxylic acid; the metal salt is a soluble metal salt; Preferably, the soluble metal salt is at least one of a soluble copper salt and a soluble iron salt.
8. A method for preparing the composite material according to any one of claims 1 to 7, comprising the steps of: S1. Preparation of porous microspheres: using fumed silica, cellulose and phthalocyanine as main raw materials to prepare porous microspheres; S2, amino modification: uniformly mixing the porous microspheres with an aqueous urea solution and heating and drying, and then performing a dry amino modification reaction to obtain amino-modified porous microspheres; S3, in situ growth of MOFs: adding the amino-modified porous microspheres and pyridine carboxylic acid ligands to a metal salt aqueous solution, heating and stirring until the pyridine carboxylic acid ligands are completely dissolved, cooling to room temperature to react, and obtaining a MOFs-porous microsphere composite material.
9. The preparation method according to claim 8, characterized in that: The step S2 comprises firstly mixing the porous microspheres with a urea aqueous solution, and drying them by rotary evaporation until the moisture content is less than 10%, and then performing a dry amino modification reaction at 130° C. to 170° C. for 2 to 8 hours to obtain the amino-modified porous microspheres; Preferably, the reaction temperature of the dry amino modification reaction is 140° C. to 170° C., and the reaction time is 4 to 7 h.
10. The preparation method according to claim 8 or 9, characterized in that: The step S3 comprises firstly adding the amino-modified porous microspheres and the pyridine carboxylic acid ligands to the metal salt aqueous solution in sequence, heating and stirring at 45° C. to 55° C. until the pyridine carboxylic acid ligands are completely dissolved, cooling to room temperature to react for 2 to 5 days, filtering, washing with water, and vacuum drying to obtain the MOFs-porous microsphere composite material.
11. Use of the composite material according to any one of claims 1 to 7 in preparing a nicotine adsorption material; Preferably, the minimum saturated adsorption capacity of nicotine by 1 g of the composite material is 100 mg / g; More preferably, the saturated adsorption capacity of nicotine by 1 g of the composite material is 100-300 mg / g.
12. Use of the composite material according to any one of claims 1 to 7 in the preparation of 3-vinylpyridine adsorption material; Preferably, the minimum saturated adsorption capacity of 3-vinylpyridine by 1 g of the composite material is 75 mg / g; More preferably, the saturated adsorption capacity of 3-vinylpyridine by 1 g of the composite material is 75 to 250 mg / g.
13. Use of the composite material according to any one of claims 1 to 7 in the preparation of environmental flue gas purification materials; Preferably, the minimum saturated adsorption capacity of nicotine and 3-vinylpyridine by 1 g of the composite material is 100 mg / g and 75 mg / g, respectively; More preferably, the saturated adsorption capacity of nicotine and 3-vinylpyridine per 1 g of the composite material is 100-300 mg / g and 75-250 mg / g, respectively.
